The Effect of Intellectual Capital, Size of the Sharia Supervisory Board and Islamicity Performance Index on Profitability - Tukhfatul Aeny; Iwan Fakhruddin; Suryo Budi Santoso; Ira Hapsari (Jurnal Multidisiplin Madani, 2023)
This study aims to determine the effect of intellectual capital, the size of the sharia supervisory board, and the Islamicity performance index which is proxied by the profitsharing ratio and the zakat performance ratio on profitability which is proxied by Return on Assets (ROA) in Islamic Commercial Banks in Indonesia. This research uses a quantitative approach. The population of this study is Islamic Commercial Banks in Indonesia that are registered with the Financial Services Authority (OJK) for the 2017-2021 period and the sample size is 15 banks. Data processing in this study used the STATA 17 program. The analytical method used in this study was the panel data regression analysis model. The results of this study indicate that the Intellectual Capital and Zakat Performance Ratio variables have a positive effect on profitability. Meanwhile, the size of the Sharia Supervisory Board and ProfitSharing Ratio has no effect on Profitability